Pengaruh Modal Sendiri, Jumlah Anggota Terhadap Pertumbuhan Koperasi Di Kota Pematangsiantar - Supitriyani Supitriyani; Khairul Azwar; Elly Susanti; Astuti Astuti (ITB AAS INDONESIA, 2021)
The purpose of this research is to determine the effect of own capital and the number of members partially and simultaneous on the growth of cooperatives (SHU) in Pematangsiantar City Cooperative in 2017-2019 periods. Data collection in this study is conducted by interview, observation and documentation methods. The sampling technique uses purposive sampling. The number of samples in this study were 17 cooperatives with the 2017-2019 periods with population of 86. The analysis techniques have been carried outusing simple and multiple linear regression, with the program SPSS 21. The partial test results of the t test show that own capital has a positive and significant effect on SHU while the number of members has a negative and significant effect on SHU. Meanwhile the results simultaneous testing hrough the F test shows that the own capital and the number of members have a positive and significant effect on SHU. The results of the determinant test have an adjusted R square (R2) value of 0.227 which means that the effect of own capital and the number of members on SHU is 22.7% and the remaining 77.3% is explained by variables or other factors not examined in this study, such as loan capital, total deposits, business volume and total assets. Keywords : Own Capital, Number of Members, SHU